Dissipative preparation of a steady three-dimensional entangled state via quantum-jump-based feedback - 陈丽 王洪福 张寿 (Chinese physics B, 2014)
A robust and scalable scheme to generate a steady three-dimensional entangled state for a V-type atom and a A- type atom trapped in a strongly dissipative bimodal cavity is proposed by direct feedback control based on quantum-jump detection. The robustness of this scheme reflects in the insensitivity to detection inefficiencies and the strong ability against the parameter fluctuations in the feedback, driving, and coupling strengths. The influence of atomic spontaneous emission can be suppressed by using the local feedback control. The scalability is ensured that N-dimensional entangled states of two atoms can be deterministically generated.